Regime-switching effect of tourism specialization on economic growth in Asia Pacific countries - Geng-Nan Chiang; Wei-Ying Sung; Wen-Guu Lei (Economies, 2017)
In the past 30 years, many studies have focused on exploring the relationship between tourism development and economic growth. However, there has been no consensus reached concerning of the relationship. This study will attempt to clarify the relationship between tourism development and economic growth. The purpose of this study is to analyze the relationship between tourism development and economic growth. This study applies the Panel Smooth Transition Regression Model (PSTR) proposed by Gonzalez et al. (2005) to investigate the regime-switching effect of tourism specialization on economic growth in Asia Pacific countries over the period 1996-2009. The results are as follows: (a) there were regime-switching effects of tourism specialization on economic growth; (b) the tourism specialization on economic growth has a better explanation for the effects of non-linear PSTR than linear PLS (Panel Least Squares); (c) in medium degree of tourism specialization countries (the value is between 0.0123~0.01663), tourism development has a significantly positive influence on economic growth, but consumption ability and investment ratios have a significantly negative influence on economic growth; (d) in low or high degree of tourism specialization countries (the value is below 0.0123 or above 0.01663), tourism development has a reduced influence on economic growth, and significantly positive influence on consumption ability and investment ratios. On the basis of these results, this study presents policy recommendations and areas for future research.
Keywords: R11; 330; tourism specialization; real international tourism receipts growth (% of GDP); economic growth; regime-switching effect; Asia Pacific countries; Panel Smooth Transition Regression Model (PSTR)